Structural inequalities as limits to remunerative equity. The case of the main metropolitan region of Argentina (1974-2018) (Desarrollo Económico. Revista de Ciencias Sociales, 2024)
The paper examines the changes in wage inequality, throughout different periods of economic policies, in the Buenos Aires Metropolitan Area, which includes the City of Buenos Aires and twenty-four districts of the Province of Buenos Aires. The central thesis is that in order to achieve a thorough understanding of the distribution of labor remunerations, it is necessary to consider the productive heterogeneity in terms of its effects on the social structure of work and the way in which the different historical-structural cleavages condition that relationship. From this perspective, the persistence of an unbalanced productive structure conditions labor insertion and the hourly remunerations originated by such In order to examine inequality in labor remunerations and their changes over time, the paper applies a decomposition model of workers’ hourly labor remunerations, considering intra- and inter-inequality, as well as the relative sizes of the economic-occupational locations. The analysis is limited to the period 1974-2018, accounting for differentiated effects according to the political-economic regime of the different subperiods.
Keywords: Occupational Structure, Income Inequality, Structural Heterogeneity